Resin composition, cured product, antenna element, and electronic component
By using specific resin compositions in high-frequency communication devices, including polyimide, polybenzoxazole and inorganic particles, combined with ester-based solvents and thermosetting resins, the dielectric of insulating film materials in high-frequency communication devices is solved. The problem of difficulty in controlling losses and linear thermal expansion properties has been achieved, and the coating properties and packaging reliability are improved.
Patent Information
- Application Number
- CN202380040466.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-23
- Filing Date
- 2023-05-16
- Publication Date
- 2025-01-10
AI Technical Summary
It is difficult for existing insulating film materials to achieve low dielectric loss and low linear thermal expansion in high-frequency communication devices, and there are problems of coating non-uniformity and increased dielectric loss.
A resin composition is adopted, including a polyimide, polybenzoxazole and its copolymer, an inorganic particle having an average particle diameter of 150 nm or more and 5 μm or less, and an ester-based solvent, and a specific diamine residue content and The solvent ratio, combined with the thermosetting resin, forms an insulating film with low dielectric loss and low linear thermal expansion.
It realizes low dielectric loss and low linear thermal expansion in high-frequency communication devices, improves coating properties and stability of the insulating film, reduces warpage and dielectric loss, and enhances packaging reliability.
Smart Images

Figure CN119301200A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition, a cured product, an antenna element and an electronic component. Background Art
[0002] Typical materials for surface protection films or interlayer insulating films of semiconductor elements, insulating layers of organic electric field elements, and planarizing films of thin film transistor (TFT) substrates include polyimide resins having excellent heat resistance and electrical insulating properties.
[0003] In recent years, with the expansion of semiconductor applications and the improvement of performance, efforts have been made to reduce costs and achieve high integration based on the efficiency of manufacturing processes. Therefore, semiconductor devices that form multilayer metal redistribution have attracted attention. In particular, in the use of high-frequency communication devices for high-speed wireless communication, in order to reduce transmission losses, low dielectric loss tangent of the insulating film is required. In addition, due to the multilayering of metal wiring, low linear thermal expansion of the insulating film is required to reduce the amount of warping.
[0004] For the low linear thermal expansion of the insulating film, a method of high filling of inorganic particles can be cited. For example, the following examples can be cited: an example of low dielectric loss tangent and low linear thermal expansion by including silica particles in a polyimide made of aliphatic diamine compounds derived from dimer acids (dimer fatty acids) and the like showing low dielectric loss tangent (Patent Document 1); or an example of a coating material showing a low linear thermal expansion coefficient by adding nano-silica having an average particle size of less than 0.1 μm (Patent Document 2).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2021-105146
[0008] Patent Document 2: Japanese Patent Application Publication No. 2018-36329 Summary of the invention
[0009] Problems to be solved by the invention
[0010] Insulating films used in the above applications are required to have various thicknesses. Therefore, compared to sheet materials with limited thickness, coating materials that can be made into thin films and whose thickness can be easily adjusted by the rotation speed during coating are required.
[0011] However, when the prior art is used as a coating material, it is difficult to form a uniform film due to the cohesion or thixotropy of the silicon dioxide particles, such as in Patent Document 1. In addition, in Patent Document 2, there are problems such as the linear thermal expansion coefficient cannot be fully reduced or the hydroxyl groups on the surface deteriorate the dielectric loss tangent due to the large specific surface area of nano silicon dioxide.
[0012] Technical means of solving problems
[0013] In order to solve the above problems, the present invention relates to the following. [1]
[0015] A resin composition comprising:
[0016] (A) a resin comprising at least one selected from the group consisting of polyimide, polybenzoxazole, their precursors, polyamide, and copolymers thereof;
[0017] (B) inorganic particles having an average particle size of 150 nm or more and 5 μm or less; and
[0018] (C) an ester solvent,
[0019] The component (A) contains a diamine residue represented by the following formula (1) and / or a diamine residue represented by the following formula (2).
[0020] When the content of the component (B) in the resin composition is represented by Bm (mass), and the content of the component (C) is represented by Cm (mass), 0.1≦(Bm / Cm)≦3.0 is satisfied.
[0021] [Chemistry 1]
[0022]
[0023] In formula (1), a, b, c and d are integers of 1 or more satisfying a+b=6 to 17 and c+d=8 to 19, and the dotted line portion indicates a carbon-carbon single bond or a carbon-carbon double bond.
[0024] [Chemistry 2]
[0025]
[0026] In formula (2), e, f, g and h are integers of 1 or more satisfying e+f=6 to 17, g+h=8 to 19, and the dotted line portion indicates a carbon-carbon single bond or a carbon-carbon double bond. [2]
[0028] The resin composition according to [1], wherein the total content of the diamine residue represented by the formula (1) and the diamine residue represented by the formula (2) in 100 mol% of all diamine residues in the component (A) is in the range of 1 mol% to 30 mol%. [3]
[0030] The resin composition according to [1] or [2], wherein the content of the component (B) is 50% by mass or more and 80% by mass or less when the solid content in the resin composition is 100% by mass. [4]
[0032] The resin composition according to any one of [1] to [3], wherein the content of the component (C) is 40% by mass or more when the total amount of the solvent in the resin composition is 100% by mass. [5]
[0034] The resin composition according to any one of [1] to [4], wherein the component (C) contains a glycol ester solvent. [6]
[0036] The resin composition according to any one of [1] to [5], wherein the component (C) is a glycol ester solvent, and when the total amount of the solvent in the resin composition is 100% by mass, the content of the component (C) is 40% by mass or more. [7]
[0038] The resin composition according to any one of [1] to [6], wherein the component (B) is inorganic particles having an average particle diameter of 150 nm or more and 1 μm or less. [8]
[0040] The resin composition according to any one of [1] to [7], wherein the resin composition further contains a thermosetting resin as component (D), wherein the component (D) contains one or more selected from the group consisting of polyphenylene ether resin, maleimide resin, polybutadiene resin, and benzocyclobutene resin. [9]
[0042] A cured product obtained by curing the resin composition according to any one of [1] to [8].
[10]
[0044] An electronic component comprising the hardened material according to [9].
[11]
[0046] An electronic component comprising two or more layers of wiring and an insulating film, wherein the insulating film is arranged between the two or more layers of wiring, and the insulating film is the cured product according to [9].
[12]
[0048] An antenna element comprises at least one antenna wiring, a ground, and an insulating film for insulating the ground from the antenna wiring, wherein:
[0049] The antenna wiring includes at least one selected from the group consisting of a zigzag loop antenna, a coiled loop antenna, a zigzag monopole antenna, a zigzag dipole antenna and a microstrip antenna,
[0050] The dedicated area of each antenna part in the antenna wiring is 1000mm 2 the following,
[0051] The insulating film is a cured product according to [9].
[13]
[0053] An electronic component includes a semiconductor package including at least a semiconductor element, a redistribution layer, a sealing resin, a ground wiring and an antenna wiring, wherein:
[0054] The redistribution layer includes copper wiring and an insulating film, and the sealing resin is located between the ground wiring and the antenna wiring.
[0055] The insulating layer of the redistribution layer and / or the sealing resin is a cured product according to [9].
[0056] Effects of the Invention
[0057] The present invention provides a resin composition having excellent coating properties on a substrate, a low dielectric loss tangent, and a low linear thermal expansion coefficient, and a cured product obtained from the resin composition, an insulating film, an antenna element, and an electronic component. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] [ Figure 1 ] is a schematic diagram of an example of a coplanar-powered microstrip antenna, which is a type of planar antenna.
[0059] [ Figure 2 ] is a schematic cross-sectional view of an example of a semiconductor package including an integrated circuit (IC) chip (semiconductor element), a redistribution layer, a sealing resin and an antenna element. DETAILED DESCRIPTION
[0060] The present invention is described in detail below.
[0061] The resin composition of the present invention comprises: (A) a resin comprising at least one selected from the group consisting of polyimide, polybenzoxazole, their precursors, polyamide and their copolymers;
[0062] (B) inorganic particles having an average particle size of 150 nm or more and 5 μm or less; and
[0063] (C) an ester solvent,
[0064] The component (A) contains a diamine residue of formula (1) and / or a diamine residue of formula (2),
[0065] When the content of the component (B) is represented by Bm (mass), and the content of the component (C) is represented by Cm (mass), 0.1≦(Bm / Cm)≦3.0 is satisfied.
[0066] [Chemistry 3]
[0067]
[0068] In formula (1), a, b, c and d are integers of 1 or more satisfying a+b=6 to 17 and c+d=8 to 19, and the dotted line portion indicates a carbon-carbon single bond or a carbon-carbon double bond.
[0069] [Chemistry 4]
[0070]
[0071] In formula (2), e, f, g and h are integers of 1 or more satisfying e+f=6 to 17, g+h=8 to 19, and the dotted line portion indicates a carbon-carbon single bond or a carbon-carbon double bond.
[0072] <(A) Resin containing at least one selected from the group consisting of polyimide, polybenzoxazole, precursors thereof, polyamide, and copolymers thereof>
[0073] The resin composition of the present invention contains (A) a resin comprising at least one selected from the group consisting of polyimide, polybenzoxazole, precursors thereof, polyamide, and copolymers thereof (hereinafter sometimes referred to as component (A)). In the present invention, "copolymers thereof" means copolymers obtained by copolymerizing two or more selected from the group consisting of polyimide, polybenzoxazole, precursors thereof, and polyamide.
[0074] Polyimide, polyamide, a polyimide precursor, polybenzoxazole, and a polybenzoxazole precursor are described.
[0075] The polyimide precursor is not particularly limited as long as it has a structure that can be converted into a polyimide having an imide ring by undergoing dehydration ring closure.
[0076] The polyimide precursor can be a polyimide precursor obtained by reacting tetracarboxylic acid, corresponding tetracarboxylic dianhydride or tetracarboxylic diester dichloride, etc. with diamine, corresponding diisocyanate compound or trimethylsilylated diamine, etc., and has tetracarboxylic acid and / or its derivative residue, diamine and / or its derivative residue. As the polyimide precursor, for example, polyamic acid, polyamic acid ester, polyamic acid amide or polyisoimide can be cited.
[0077] The polyimide is not particularly limited as long as it has an imide ring.
[0078] As polyimide, for example, polyimide obtained by dehydrating and ring-closing the polyamic acid, polyamic acid ester, polyamic acid amide or polyisoimide by heating or reaction with acid or alkali, etc., and having tetracarboxylic acid and / or its derivative residue, diamine and / or its derivative residue. In addition, copolymers can also be prepared by adjusting the reaction time during the dehydration and ring-closing process, or by continuously polymerizing the polyamic acid after polymerizing the polyimide.
[0079] The polyamide is not particularly limited as long as it has an amide bond.
[0080] Examples of the polyamide include polyamides obtained by reacting dicarboxylic acid, corresponding dicarboxylic acid dichlorides or dicarboxylic acid active diesters with diamines, corresponding diisocyanate compounds or trimethylsilylated diamines, and polyamides having dicarboxylic acid and / or derivative residues thereof, and diamine and / or derivative residues thereof.
[0081] The polybenzoxazole precursor is not particularly limited as long as it has a structure that can be converted into a polybenzoxazole having a benzoxazole ring by undergoing dehydration ring closure.
[0082] Examples of polybenzoxazole precursors include those obtained by reacting dicarboxylic acid, corresponding dicarboxylic acid dichloride or dicarboxylic acid active diester with bisaminophenol compound as diamine, and having dicarboxylic acid and / or its derivative residue, bisaminophenol compound and / or its derivative residue. Examples of polybenzoxazole precursors include polyhydroxyamide.
[0083] The polybenzoxazole is not particularly limited as long as it has a benzoxazole ring.
[0084] Examples of polybenzoxazole include polybenzoxazole obtained by dehydrating and ring-closing a dicarboxylic acid and a bisaminophenol compound as a diamine by reaction with polyphosphoric acid, or polybenzoxazole obtained by dehydrating and ring-closing the polyhydroxyamide by heating or reaction with phosphoric anhydride, alkali or carbodiimide compounds, and having a dicarboxylic acid and / or a derivative residue thereof, a bisaminophenol compound and / or a derivative residue thereof. In addition, a copolymer may be prepared by adjusting the reaction time during the dehydration ring-closing process, or by polymerizing a polyamide after polymerizing the polybenzoxazole.
[0085] The polyimide and / or polyimide precursor may contain tetracarboxylic acid residues and / or their derivative residues as described below. As tetracarboxylic acid residues, for example, residues of aromatic tetracarboxylic acids, alicyclic tetracarboxylic acids or aliphatic tetracarboxylic acids may be mentioned. These tetracarboxylic acid residues may have heteroatoms other than oxygen atoms in addition to the oxygen atoms having carboxyl groups.
[0086] As tetracarboxylic acid residues and their derivative residues, for example, butanetetracarboxylic acid, cyclopentanetetracarboxylic acid, pyromellitic acid, dicyclohexanetetracarboxylic acid, pentanetetracarboxylic acid, hexanetetracarboxylic acid, cyclopropanetetracarboxylic acid, cyclobutanetetracarboxylic acid, cyclopentanetetracarboxylic acid, cyclohexanetetracarboxylic acid, 3,3',4,4'-benzophenonetetracarboxylic acid, 3,3',4,4'-diphenylsulfonetetracarboxylic acid, 4,4'-oxydiphthalic acid, 4,4'-(hexafluoroisopropylidene)diphthalic acid, 3,3',4,4'-biphenyltetracarboxylic acid, 4,4'-(4,4'-isopropylidenediphenyloxy)diphthalic acid and other compounds, or tetracarboxylic acid dianhydrides, tetracarboxylic acid dichlorides or tetracarboxylic acid active diesters thereof, but are not limited thereto. The polyimide and / or polyimide precursor may contain these residues alone or in combination of two or more thereof.
[0087] As dicarboxylic acid residues and their derivative residues in polyamide, polybenzoxazole and polybenzoxazole precursor, tricarboxylic acid residues and / or their derivative residues may also be contained. As dicarboxylic acid residues and tricarboxylic acid residues, for example, residues of aromatic dicarboxylic acids, aromatic tricarboxylic acids, alicyclic dicarboxylic acids, alicyclic tricarboxylic acids, aliphatic dicarboxylic acids or aliphatic tricarboxylic acids may be listed. These dicarboxylic acid residues and tricarboxylic acid residues may also have heteroatoms other than oxygen atoms in addition to the oxygen atoms of the carboxyl group.
[0088] Examples of dicarboxylic acid residues and their derivative residues include, but are not limited to, residues of phthalic acid, isophthalic acid, terephthalic acid, 4,4'-dicarboxybiphenyl, 2,2'-bis(trifluoromethyl)-4,4'-dicarboxybiphenyl, 4,4'-benzophenonedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, hexane-1,6-dicarboxylic acid, succinic acid, or dicarboxylic acid anhydrides, dicarboxylic acid chlorides, dicarboxylic acid active esters, or diformyl compounds thereof.
[0089] Examples of the tricarboxylic acid residue and its derivative residue include, but are not limited to, residues of 1,2,4-benzenetricarboxylic acid, 1,3,5-benzenetricarboxylic acid, 2,4,5-benzophenonetricarboxylic acid, 2,4,4'-biphenyltricarboxylic acid, 3,3',4'-tricarboxydiphenyl ether, 1,2,4-cyclohexanetricarboxylic acid, 1,3,5-cyclohexanetricarboxylic acid, or tricarboxylic anhydrides, tricarboxylic acid chlorides, tricarboxylic acid active esters, or diformylmonocarboxylic acids.
[0090] Examples of diamine residues and their derivative residues include residues of aromatic diamines, bisaminophenol compounds, alicyclic diamines, alicyclic dihydroxy diamines, aliphatic diamines, or aliphatic dihydroxy diamines. These diamine residues and their derivative residues may have heteroatoms in addition to nitrogen atoms and oxygen atoms possessed by amino groups and their derivatives.
[0091] Examples of the diamine residue and bisaminophenol compound residue and the residues of derivatives thereof include 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfide, m-phenylenediamine, p-phenylenediamine, 2,4-diaminotoluene, 2,5-diaminotoluene, 2,6-diaminotoluene, benzidine, 3,3'-dimethylbenzidine, 3,3'-dimethoxybenzidine, o-toluidine, 4,4"-diaminoterphenyl, 1,5-diaminonaphthalene, 2,5-diaminopyridine, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 1,2-cyclohexanediamine, 1,4-cyclohexanediamine, bis(4-aminocyclohexyl)methane, 3,6-dihydroxy-1,2-cyclohexanediamine, 2,5-dihydroxy-1,4-cyclohexanediamine, bis(3-hydroxy- 4-aminocyclohexyl)methane, 4,4'-bis(p-aminophenoxy)biphenyl, 2,2-bis[4-(p-aminophenoxy)phenyl]propane, hexahydro-4,7-methanoindanedimethylenediamine, 3,3'-diamino-4,4'-dihydroxybiphenyl, 4,4'-diamino-3,3'-dihydroxybiphenyl, bis(3-amino-4-hydroxyphenyl)propane, bis(4-amino-3-hydroxyphenyl)propane , bis(3-amino-4-hydroxyphenyl)sulfone, bis(4-amino-3-hydroxyphenyl)sulfone, 2,2-bis(3-amino-4-hydroxyphenyl)-1,1,1,3,3,3-hexafluoropropane, 2,2-bis(4-amino-3-hydroxyphenyl)-1,1,1,3,3,3-hexafluoropropane or the like, or diisocyanate compounds thereof or residues of trimethylsilylated diamine, but are not limited to these.
[0092] (A) Component contains a diamine residue of formula (1) and / or a diamine residue of formula (2).
[0093] The diamine residue of formula (1) or the diamine residue of formula (2) has a structure having a skeleton of a dimer acid derived from a dimer of an unsaturated fatty acid such as linoleic acid or oleic acid. From the viewpoint of the reliability of the obtained cured product, a structure having no double bond is preferred. From the viewpoint of economic efficiency and the elongation of the obtained cured product, a structure represented by formula (3) is particularly preferred.
[0094] [Chemistry 5]
[0095]
[0096] Specific examples of the diamine having a structure represented by formula (3) include commercially available dimer diamine products such as "Versamine (registered trademark)" 551 and "Versamine (registered trademark)" 552 manufactured by BASF (Co., Ltd.), and "Priamine (registered trademark)" 1073, "Priamine (registered trademark)" 1074, and "Priamine (registered trademark)" 1075 manufactured by Croda Japan (Co., Ltd.). Here, "Versamine (registered trademark)" 551 and "Priamine (registered trademark)" 1074 are both dimer diamine compounds containing the compound represented by formula (4), and "Versamine (registered trademark)" 552, "Priamine (registered trademark)" 1073 and "Priamine (registered trademark)" 1075 are all dimer diamine compounds containing the compound represented by formula (3).
[0097] [Chemistry 6]
[0098]
[0099] In addition, a mixture of trimer triamine and dimer diamine can also be used. Examples of commercially available products of trimer triamine and dimer diamine include "Priamine (registered trademark)" 1071 manufactured by Croda Japan Co., Ltd.
[0100] The component (A) preferably contains 1 mol % to 30 mol % in total of the diamine residues of the formula (1) and the diamine residues of the formula (2), based on 100 mol % of all diamine residues of the component (A), and more preferably 1 mol % to 15 mol %.
[0101] When the component (A) contains 1 mol % or more in total of the diamine residues of the formula (1) and the diamine residues of the formula (2) in 100 mol % of all the diamine residues of the component (A), the relative dielectric constant and the dielectric loss tangent can be reduced.
[0102] When the component (A) contains 30 mol% or less in total of the diamine residues of the formula (1) and the diamine residues of the formula (2) in 100 mol% of all the diamine residues of the component (A), the linear thermal expansion coefficient can be reduced.
[0103] In addition, in order to improve the storage stability of the resin composition, (A) component is preferably sealed by end-capping agents such as monoamine, acid anhydride, monocarboxylic acid, monoacyl chloride compound, and monoactive ester compound. In addition, by using end-capping agents with hydroxyl, carboxyl, sulfonic acid, thiol, vinyl, ethynyl, or allyl groups to seal the end of (A) component, the solubility of the resin in the solvent and the mechanical properties of the obtained hardened material can be easily adjusted to a preferred range. Relative to 100 molar parts of all amine components of (A) component, in order to suppress the molecular weight of (A) component to become high and the solubility in the solvent to reduce, the introduction ratio of the end-capping agent is preferably more than 0.1 molar parts, and is particularly preferably more than 5 molar parts. In addition, in order to suppress the mechanical properties of the obtained hardened material to reduce by making the molecular weight of (A) component lower, the introduction ratio of the end-capping agent is preferably less than 60 molar parts, and is particularly preferably less than 50 molar parts. A variety of different end groups can be introduced by reacting a variety of end-capping agents.
[0104] As the monoamine, acid anhydride, monocarboxylic acid, monoacid chloride compound, and monoactive ester compound, the compounds described in Japanese Patent No. 6740903
[0038] to
[0042] can be used.
[0105] In the present invention, the end-capping agent introduced into the component (A) can be easily detected by gas chromatography (GC), pyrolysis gas chromatograph (PGC), infrared spectroscopy and / or nuclear magnetic resonance (NMR) measurement.
[0106] (A) component preferably has a weight average molecular weight of 5,000 or more and 100,000 or less. If the weight average molecular weight is 8,000 or more, the mechanical properties of the cured product after curing can be improved. More preferably, the weight average molecular weight is 12,000 or more. On the other hand, as long as the weight average molecular weight is 100,000 or less, the solubility in organic solvents can be improved, and further as long as the weight average molecular weight is 50,000 or less, the viscosity when dissolved in an organic solvent can be within an appropriate range, so it is preferred.
[0107] The weight average molecular weight (Mw) can be confirmed by gel permeation chromatography (GPC). For example, the developing solvent can be set to N-methyl-2-pyrrolidone (hereinafter sometimes referred to as NMP (N-methyl-2-pyrrolidone)) for measurement and calculated by polystyrene conversion. In addition, when two or more resins are contained as (A) resin, the weight average molecular weight of at least one of them can be within the above range.
[0108] <(B) Inorganic particles having an average particle size of 150 nm or more and 5 μm or less>
[0109] Resin combination of the present invention contains (B) average particle diameter more than 150nm and inorganic particles below 5μm (hereinafter sometimes referred to as (B) component). By containing (B) component, the thermal expansion coefficient and dielectric loss tangent of the hardened material can be reduced without damaging the coating property. As the material of inorganic particles, two or more metal sulfates such as silicon dioxide, hollow silicon dioxide, aluminum oxide, titanium dioxide, silicon nitride, boron nitride, aluminum nitride, iron oxide, glass or other metal oxides, metal nitrides, metal carbonates, barium sulfate, etc. can be used alone or in combination. Among these, with respect to low linear thermal expansion, low dielectric loss tangent, low moisture absorption, silicon dioxide can be preferably used.
[0110] From the viewpoint of suppressing agglomerates or improving coating properties, the average particle size of component (B) is 5 μm or less, more preferably 2 μm or less, and further preferably 1 μm or less. On the other hand, from the viewpoint of low linear thermal expansion or low dielectric loss tangent, the average particle size is 150 nm or more, preferably 300 nm or more. As the average particle size, the median particle size (d 50 The average particle size can be measured using a particle size distribution measuring device using a laser diffraction scattering method.
[0111] (B) component is preferably surface treated, more preferably a surface treated product using a coupling agent, and further preferably a surface treated product using a silane coupling agent. Thus, when deployed in a resin composition, dispersibility is improved and coating properties are improved. As the coupling agent, silane coupling agents, titanium coupling agents and aluminum coupling agents can be listed. As the silane coupling agent, methacrylic silane, acrylic silane, aminosilane, phenylaminosilane, imidazole silane, vinyl silane and epoxy silane, etc., more preferably aminosilane and phenylaminosilane.
[0112] When the solid content in the resin combination is set to 100 mass %, with respect to the viewpoint of low linear thermal expansion or low dielectric loss tangent, the content of (B) component is preferably more than 50 mass %, more preferably more than 60 mass %.On the other hand, with respect to the viewpoint of suppressing agglomerates or improving coating properties, it is preferably below 80 mass %, more preferably below 70 mass %.Solid content refers to the component after removing the solvent in the resin combination.
[0113] <(C) Ester-based solvent>
[0114] The resin composition of the present invention contains (C) an ester solvent (hereinafter sometimes referred to as (C) component).
[0115] (C) ester solvent refers to a solvent having an ester bond and a molecular weight of less than 1000. For example, (C) component can include: ethyl acetate, butyl acetate, isobutyl acetate, sec-butyl acetate, methoxybutyl acetate, amyl acetate, n-propyl acetate, isopropyl acetate, methyl lactate, ethyl lactate, butyl lactate, 3-methyl-3-methoxybutyl acetate, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, butyl carbitol acetate, ethyl carbitol acetate, etc., but are not limited to these. The resin composition can contain these ester solvents alone or in combination of two or more. In addition, (C) component is preferably a linear ester solvent.
[0116] It is more preferred that component (C) contains a glycol ester solvent. In addition, it is further preferred that component (C) consists only of a glycol ester solvent. A glycol ester solvent refers to a solvent having a structure in which one or both of the hydroxyl groups of a glycol are esterified. Among them, component (C) is preferably alkylene glycol monoalkyl ether acetate, more preferably ethylene glycol monomethyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate. By including component (C), component (B) in the resin composition can be stabilized in the resin composition system, thereby greatly improving the coating properties.
[0117] When the total amount of the solvent in the resin composition is 100% by mass, the content of the component (C) is preferably 40% by mass or more, more preferably 70% by mass or more, and further preferably 100% by mass. The greater the content of the component (C), the more the dispersion stability of the component (B) is improved.
[0118] In addition, the resin composition of the present invention may also contain solvents other than component (C). For example, polar aprotic solvents such as N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, 1,3-dimethyl-2-imidazolidinone, N,N'-dimethylpropyleneurea, N,N-dimethylisobutyric acid amide, methoxy-N,N-dimethylpropionamide, tetrahydrofuran, dioxane, propylene glycol monomethyl ether, propylene glycol monoethyl ether, ketones such as acetone, methyl ethyl ketone, diisobutyl ketone, alcohols such as diacetone alcohol, 3-methyl-3-methoxybutanol, aromatic hydrocarbons such as toluene and xylene, etc. can be listed. The resin composition may also contain two or more of these.
[0119] The content of the solvent is preferably 30 parts by mass or more based on 100 parts by mass of the solid content in order to easily dissolve the composition, and is preferably 1,500 parts by mass or less in order to easily form a coating film having a thickness of 1 μm or more.
[0120] The resin composition of the present invention, when the content of the (B) component is set to Bm (mass) and the content of the (C) component is set to Cm (mass), is 0.1≦(Bm / Cm)≦3.0, more preferably 0.1≦(Bm / Cm)≦2.4, and further preferably 0.1≦(Bm / Cm)≦1.8. It is found that the ratio of the (B) component to the (C) component is important for coating properties, and it is known that a certain (C) component is required relative to the (B) component. Therefore, by setting the range of 0.1≦(Bm / Cm)≦3.0, the resin composition system of the (B) component can be stabilized, thereby greatly improving coating properties.
[0121] <(D) Thermosetting resin>
[0122] The resin composition of the present invention further contains (D) a thermosetting resin (hereinafter, sometimes referred to as component (D)), wherein the component (D) preferably contains one or more selected from the group consisting of polyphenylene ether resin, maleimide resin, polybutadiene resin, and benzocyclobutene resin. When these resins are used, since they have low polarity, they can improve chemical resistance while having good compatibility with component (A), good coating properties, and low dielectric loss tangent.
[0123] The polyphenylene ether resin is not particularly limited as long as it is a resin that repeatedly contains the structure described in formula (5) in the resin structure. It is preferably a form having a plurality of structures described in formula (5) in the resin structure, and is particularly preferably a form containing the largest number of structures described in formula (5) as the number of repeating units in the resin structure. In addition, the polyphenylene ether resin referred to in the present invention may be a copolymer with other structures as long as it is a resin that contains the structure described in formula (5) in the resin structure.
[0124] [Chemistry 7]
[0125]
[0126] In formula (5), R 1 ~R 4 They may be the same or different and represent a hydrogen atom, a halogen atom, or an alkyl group, an alkoxy group, a fluoroalkyl group, a phenyl group, or a phenoxy group having 1 to 30 carbon atoms.
[0127] The number average molecular weight of the polyphenylene ether resin is preferably 500 or more and 5000 or less. More preferably, it is 1000 or more and 4000 or less. By making the number average molecular weight 500 or more, the crosslinking density can be reduced and the toughness of the resin composition can be improved. By making it 5000 or less, the compatibility with other components such as polyimide can be improved, and the thermosetting resin composition can be made into a uniform structure, thereby stabilizing the physical properties. The crosslinking functional groups of the polyphenylene ether resin can be listed as phenolic hydroxyl, acrylic group, vinyl group, and epoxy group, but are not limited to these. These crosslinking functional groups are preferably attached to both ends of the molecular chain, but can also be attached only to the end of one side. The crosslinking functional groups contained in the phenylene ether resin are preferably vinyl groups in these crosslinking functional groups. The thermosetting resin composition obtained by thermal crosslinking using vinyl groups has low polarity, so the relative dielectric constant and dielectric loss tangent can be reduced. As such resins, OPE-2st manufactured by Mitsubishi Gas Chemical (stock) can be listed.
[0128] From the viewpoint of reducing the viscosity of the thermosetting resin composition solution, the maleimide resin is not particularly limited as long as it is soluble in an organic solvent. Examples of the maleimide resin include phenylmethane maleimide, metaphenylene bismaleimide, 4,4′-diphenylmethane bismaleimide, bis(3-ethyl-5-methyl-4-maleimidophenyl)methane, 2,2′-bis[4-(4-maleimidophenoxy)phenyl]propane, 4-methyl-1,3-phenylene bismaleimide, 1,6-bismaleimide-(2,2,4-trimethyl)hexane, 4,4-diphenyl ether bismaleimide, 4,4-diphenyl sulfone bismaleimide, polyphenylmethane maleimide, novolac-type maleimide compounds, biphenyl aralkyl-type maleimide compounds, and prepolymers of these maleimide resins.
[0129] The polybutadiene resin is not particularly limited as long as it contains the structure represented by formula (6) in the resin structure, but preferably has a form in which the resin structure has a plurality of structures represented by formula (6).
[0130] [Chemistry 8]
[0131]
[0132] The average molecular weight of the polybutadiene resin is preferably 500 to 5000. Examples of such polybutadiene resins include B1000, B2000, and B3000 manufactured by Nippon Soda Co., Ltd., and Ricon 130, Ricon 131, Ricon 142, Ricon 150, Ricon 152, Ricon 153, Ricon 156, Ricon 157, Ricon 130MA8, Ricon 130MA13, Ricon 130MA20, Ricon 156MA17, Ricon 100, and Ricon 181 manufactured by Total Lubricants Japan Co., Ltd.
[0133] The benzocyclobutene resin is produced, for example, by reacting a brominated arylcyclobutene compound with a compound containing an unsaturated alkyl group in the presence of a palladium catalyst. Specifically, divinylsiloxane bisbenzocyclobutene and the like are exemplified. In addition, commercially available benzocyclobutene compounds include CYCLOTENE 3022-63 and 4026-46 manufactured by Dow Chemical.
[0134] The content of the component (D) is 1% by mass or more and 50% by mass or less, and more preferably 10% by mass or more and 30% by mass or less, in 100% by mass of the total amount of the resin. The component (D) may contain these alone or in combination of two or more.
[0135] <Thermal cross-linking agent>
[0136] The resin composition of the present invention may also contain a thermal crosslinking agent. As the thermal crosslinking agent, a known thermal crosslinking agent can be used. For example, compounds containing at least two or more groups selected from the group consisting of acrylic acid group, methacrylic acid group, maleimide group, styryl group, epoxy group, oxetanyl group, benzoxazine structure, alkoxymethyl group and hydroxymethyl group can be mentioned, but it is not limited thereto.
[0137] The content of the thermal crosslinking agent is 1% by mass or more and 50% by mass or less, and more preferably 3% by mass or more and 40% by mass or less, based on 100% by mass of the total amount of the resin. The thermal crosslinking agent may be contained alone or in combination of two or more.
[0138] <Hardening accelerator>
[0139] The resin composition of the present invention may also contain a hardening accelerator. By containing a hardening accelerator, the hardening of the thermal crosslinking agent can be promoted and hardened in a short time. As a hardening accelerator, there is no particular limitation, and imidazoles, polyphenols, anhydrides, amines, hydrazides, polythiols, Lewis acid-amine complexes, latent hardeners, organic peroxides, etc. can be used. Among them, it is preferred to use imidazoles and organic peroxides with excellent storage stability and heat resistance of the hardened material. These can be contained alone or in a mixture of two or more. As imidazoles, "Curezol (registered trademark)" 2MZ, "Curezol (registered trademark)" 2PZ, "Curezol (registered trademark)" 2MZ-A, "Curezol (registered trademark)" 2MZ-OK (the above are trade names, manufactured by Shikoku Chemical Industry (stock)) and the like. Examples of the polyphenol include: "SUMILITE Resin (registered trademark)" PR-HF3, "SUMILITE Resin (registered trademark)" PR-HF6 (these are trade names, Sumitomo Bakelite "Phenolite (registered trademark)" TD2131, "Phenolite (registered trademark)" TD2090, "Phenolite (registered trademark)" VH-4150, "Phenolite (registered trademark)" KH-6021, "Phenolite (registered trademark)" KA-1160, "Phenolite (registered trademark)" KA-1165 (the above are trade names, manufactured by DIC (Co., Ltd.)), etc. Examples of the organic peroxide include benzoyl peroxide, cumene hydroperoxide, dicumyl peroxide, diisopropylbenzene hydroperoxide, tert-butyl hydroperoxide, tert-butyl peroxyacetate, tert-butyl peroxybenzoate, tert-butyl isopropyl carbonate, di-tert-butyl peroxide, tert-butyl peroctanoate, 1,1-bis(tert-butylperoxy)3,3,5-trimethylcyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, tert-butyl peroxy-2-ethylhexanoate, etc. The content of the curing accelerator is not particularly limited, but is preferably 0.1% by mass or more and 10% by mass or less in 100% by mass of the total amount of the resin.
[0140] <Adhesion improving agent>
[0141] The resin composition of the present invention may also contain a close contact improver. Examples of the close contact improver include vinyl trimethoxysilane, vinyl triethoxysilane, epoxy cyclohexyl ethyl trimethoxysilane, 3-glycidyloxypropyl trimethoxysilane, 3-glycidyloxypropyl triethoxysilane, p-phenylyl trimethoxysilane, 3-aminopropyl trimethoxysilane, 3-aminopropyl triethoxysilane, N-phenyl-3-aminopropyl trimethoxysilane, 3-methacryloxypropyl trimethoxysilane, 3-acryloxypropyl trimethoxysilane and other silane coupling agents, titanium chelating agents, aluminum chelating agents, compounds obtained by reacting aromatic amine compounds with alkoxy-containing silicon compounds, etc., and particularly preferably trimethoxyvinyl silane, triethoxyvinyl silane, 3-methacryloxypropyl trimethoxysilane, 3-acryloxypropyl trimethoxysilane, p-phenylyl trimethoxysilane, and more preferably p-phenylyl trimethoxysilane. The close contact improving agent may contain two or more of these.
[0142] The content of the adhesion improver in the resin composition is preferably 0.1% to 10% by mass relative to 100% by mass of the total resin content. By setting the content within this range, a resin composition having high adhesion to a substrate and excellent resistance to oxygen plasma or UV ozone treatment can be provided.
[0143] <Surfactant>
[0144] The resin composition of the present invention may also contain a surfactant. By containing a surfactant, wettability with a substrate can be improved, or the film thickness uniformity of a coating film can be improved. As a surfactant, a commercially available compound can be used. Specifically, as a silicone surfactant, SH series, SD series, ST series of Toray Dow Corning silicone, BYK series of BYK Chemie Japan, KP series of Shin-Etsu Silicone, Disk Home series of Nippon Oil & Fats, TSF series of Toshiba Silicone, etc. can be cited, as a fluorine-based surfactant, "Megafac" (registered trademark) series of Dainippon Ink Industries, Fluorad series of Sumitomo 3M, "Surflon" (registered trademark) series of Asahi Glass, "Asahi Guard" (registered trademark) series of Asahi, EF series of Shin-Akita Chemical, POLYFOX series of OMNOVA Solutions, etc. can be cited. Examples of surfactants obtained from acrylic acid-based and / or methacrylic acid-based polymers include, but are not limited to, the Polyflow series of Kyoeisha Chemical Co., Ltd. and the Disparlon (registered trademark) series of Kusumoto Chemical Co., Ltd.
[0145] The content of the surfactant is preferably 0.001% by mass and 1% by mass relative to the total amount of the resin (100% by mass). By setting the content within the above range, undesirable conditions such as bubbles and pinholes will not occur, and the wettability of the resin composition and the substrate and the uniformity of the film thickness of the coating film can be improved.
[0146] <Method for producing resin composition>
[0147] Next, a method for producing the resin composition of the present invention is described. For example, the resin composition can be obtained by mixing and dissolving the components (A), (B), and (C) as described above with a curing accelerator, an adhesion improver, a surfactant, etc. as required.
[0148] As the dissolving method, heating or stirring can be cited. In the case of heating, the heating temperature is preferably set within a range that does not damage the performance of the resin composition, usually 25°C to 80°C. In addition, the dissolution order of the components is not particularly limited, and for example, a method of dissolving in sequence starting from compounds with low solubility can be cited. In the case of stirring, the rotation speed is preferably set within a range that does not damage the performance of the resin composition, usually 200rpm to 2000rpm. In the case of stirring, heating can also be performed as needed, usually 25°C to 80°C. In addition, for components such as surfactants or a portion of adhesion improvers that are prone to generate bubbles when stirred and dissolved, by dissolving other components and adding them last, poor dissolution of other components caused by the generation of bubbles can be prevented.
[0149] The viscosity of the resin composition of the present invention is preferably 2 mPa·s to 5,000 mPa·s at 25°C. By adjusting the solid content concentration so that the viscosity reaches 2 mPa·s or more, the desired film thickness can be easily obtained. On the other hand, if the viscosity is 5,000 mPa·s or less, a coating film with high uniformity can be easily obtained. The viscosity measurement here is a measurement performed using an old E-type viscometer / DVE-type viscometer of a TVE-25 type viscometer (manufactured by Toki Sangyo Co., Ltd.), and 1.1 mL of the resin composition of the present invention is collected and injected into a sample cup. According to the viscosity, the torque is selected in the range of 65 μN·m to 6000 μN·m, and the measurement is performed in the range of a rotation speed of 0.5 rpm to 100 rpm. The resin composition of the present invention having such a viscosity can be easily obtained by making the total content of the (A) component and the (B) component in 100% by mass of the resin composition of the present invention 5% by mass to 60% by mass. Here, the solid content concentration refers to the total concentration (mass %) of components other than the solvent when the total amount of the resin composition including the solvent is taken as 100 mass %.
[0150] The obtained resin composition is preferably filtered using a filter to remove dust or particles. The filter pore size is, for example, 10.0 μm, 5.0 μm, 3.0 μm, 1.0 μm, 0.5 μm, 0.2 μm, 0.1 μm, etc., but is not limited thereto. The filter material includes polypropylene (PP), polyethylene (PE), nylon (NY), polytetrafluoroethylene (PTFE), etc., but preferably polyethylene or nylon.
[0151] <Hardened material>
[0152] The hardened material of the present invention is formed by hardening the resin composition of the present invention. The hardened material of the present invention has a low dielectric loss tangent and a low linear thermal expansion coefficient. The hardened material is obtained by heating the resin composition. Heating can be performed using an oven, a hot plate, infrared rays, a flash annealing device, or a laser annealing device.
[0153] The cured product of the present invention can be produced, for example, by the following method.
[0154] First, the resin composition of the present invention is applied onto a substrate and dried to obtain a resin film. Next, the resin film is heat-treated to obtain a cured product of the present invention.
[0155] The heat treatment of the resin film can be carried out by raising the temperature in stages or by continuously raising the temperature. The heat treatment is preferably carried out for 5 minutes to 5 hours. As an example, an example of heat treatment at 140°C for 30 minutes and then at 320°C for 60 minutes can be cited. As the heat treatment temperature, it is preferably above 140°C and below 400°C. In order to remove the solvent in the resin film, the heat treatment temperature is preferably above 140°C, more preferably above 160°C. In addition, from the viewpoint of suppressing film shrinkage or stress, it is preferably below 280°C, more preferably below 250°C, and further preferably below 220°C.
[0156] The cured product of the present invention can also be used as an insulating film or a protective film. Specific examples of the insulating film or protective film include: a passivation film of a semiconductor, a surface protective film of a semiconductor element, an interlayer insulating film, an interlayer insulating film of a multilayer wiring for high-density mounting, an insulating layer of an organic electroluminescent element, etc., but are not limited thereto and various structures can be listed.
[0157] <Electronic component, antenna element, and method for manufacturing the same>
[0158] The electronic component or antenna element of the present invention includes a cured product of the resin composition of the present invention.
[0159] The method for producing an electronic component of the present invention comprises the steps of applying the resin composition of the present invention and drying it to form a resin film, patterning the resin film as necessary, and heat-treating the resin film to form a cured product.
[0160] In the process of applying the resin composition of the present invention and drying it to form a resin film, the resin composition of the present invention is first applied to a substrate to obtain a coating film of the resin composition. Examples of the substrate include, but are not limited to, silicon wafers, ceramics, gallium arsenide, organic circuit substrates, inorganic circuit substrates, and substrates on which constituent materials such as circuits are arranged.
[0161] Examples of coating methods include spin coating, slit coating, dip coating, spray coating, and printing. The coating film thickness varies depending on the coating method, solid content concentration of the composition, viscosity, etc., but is usually applied so that the film thickness after drying is 0.1 μm to 150 μm.
[0162] Before coating, the substrate to be coated with the resin composition may be pre-treated with the adhesion improver. As a pre-treatment method, for example, a solution of dissolving 0.5% to 20% by mass of the adhesion improver in a solvent such as isopropanol, ethanol, methanol, water, tetrahydrofuran, propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, ethyl lactate, diethyl adipate, etc., and treating the substrate surface by spin coating, slit die coating, rod coating, dip coating, spray coating, steam treatment, etc. After treating the substrate surface, a reduced pressure drying treatment may be performed as needed. In addition, the reaction between the substrate and the adhesion improver may be carried out by a heat treatment at 50°C to 280°C thereafter.
[0163] Next, the applied film of the resin composition is dried to form a resin film. Drying is preferably performed using an oven, a hot plate, infrared rays, or the like at 50° C. to 140° C. for 1 minute to 2 hours.
[0164] There is no particular limitation on the pattern forming method of the resin film, and examples thereof include wet etching or dry etching. Regarding dry etching, specifically, it includes: a process of applying the resin composition of the present invention on a substrate, a process of volatilizing the solvent at a temperature of 80°C or more and less than 150°C, a process of curing at a temperature of 150°C or more and less than 350°C, and a process of ablation processing by a carbonic acid laser or an ultraviolet (UV) laser. The irradiation conditions of the UV laser are not particularly limited, and excimer lasers such as ArF (193nm), KrF (248nm), XeCl (308nm), and XeCl (351nm), and yttrium aluminum garnet (yttrium aluminum garnet, YAG) laser (355nm) light are generally used. Carbonic acid lasers have poor resolution compared to UV lasers, but because the device cost is low and the economy is excellent, carbonic acid lasers can also be used in applications that do not require high precision.
[0165] One form of the electronic component of the present invention is an electronic component having two or more layers of wiring and an insulating film, wherein the insulating film is arranged between the two or more layers of wiring, and the insulating film is a cured product of the present invention. By arranging the cured product of the present invention as an insulating film between the wirings, a multilayer wiring structure can be formed in which two or more layers of redistribution are separated by an insulating film comprising a cured product of the resin composition of the present invention. Generally speaking, in a package having a multilayer wiring structure, there is a problem of applying strong stress to the insulating film and generating cracks after a package reliability test, but by using an insulating film comprising a cured product of the resin composition of the present invention, a package with high reliability in which the warping of the substrate is reduced and cracks are not generated can be obtained. There is no upper limit to the number of layers of the multilayer wiring structure, but a number of layers of 10 or less is often used.
[0166] As an example of a semiconductor device in the electronic component of the present invention, for example, a chip-first fan-out wafer-level package or a chip-first fan-out panel-level package can be cited. The chip-first fan-out wafer-level package or the chip-first fan-out panel-level package refers to a semiconductor package in which an expansion portion is provided around a semiconductor chip using a sealing resin such as an epoxy resin, and redistribution is performed from an electrode on the semiconductor chip to the expansion portion, and the required number of terminals is ensured by also carrying solder balls on the expansion portion. In the chip-first fan-out wafer-level package or the chip-first fan-out panel-level package, the wiring is provided in a manner that straddles the boundary line formed by the main surface of the semiconductor chip and the main surface of the sealing resin, and the hardened material is configured as an insulating film between the wiring.
[0167] As an example of a method for manufacturing an electronic component of the present invention, a method for manufacturing a semiconductor device using a redistribution layer (RDL: Re-distribution layer) priority process is shown. A barrier metal such as Ti is formed on a supporting substrate such as a glass substrate or a silicon wafer by a sputtering method, and then a Cu seed (seed layer) is formed thereon by a sputtering method, and then an electrode pad containing Cu is formed by a plating method. Subsequently, the resin composition of the present invention is applied to the entire surface of the supporting substrate on which the electrode pad is formed, and dried to form a resin film. Lines and spaces, square or hole-shaped patterns are formed on the obtained resin film as needed. Then, heat treatment is performed to form a layer of a cured product. The layer becomes an insulating film. Subsequently, a seed layer is formed again by a sputtering method, and a metal wiring (re-wiring) containing Cu is formed by a plating method. Hereinafter, the process from the seed layer to the process of metal wiring formation is repeated to form a multilayer wiring structure. Then, the resin composition of the present invention is applied again, and after patterning, heat treatment is performed to harden it, thereby forming an insulating film, and thereafter, a Cu column is formed on the metal wiring using a plating method at the opening of the insulating film. Here, the spacing of the Cu column is equal to the spacing of the conductive portion of the semiconductor chip. That is, the spacing of the conductive portion of the semiconductor chip is micro-distance compared to the spacing of the electrode pad. As a result, each redistribution layer constituting the multi-layer wiring structure is gradually micro-distanced from the electrode pad to the Cu column, while the wiring is multi-layered. The thickness of the adjacent insulating film in the multi-layer wiring structure also becomes the same or thinner as it approaches the semiconductor chip. Then, the semiconductor chip is connected to the Cu column via a solder bump. Thus, the electrode pad and the semiconductor chip are electrically connected via metal wiring and solder bumps. Thereafter, after the semiconductor chip is sealed by a sealing resin to make a semiconductor package, the support substrate and the redistribution layer are peeled off to separate the semiconductor package. In this way, a semiconductor device with a multi-layer wiring structure using an RDL priority process can be obtained.
[0168] The antenna element of the present invention is an antenna element including at least one antenna wiring, a ground, and an insulating film for insulating the ground from the antenna wiring.
[0169] The antenna wiring includes at least one selected from the group consisting of a zigzag loop antenna, a coiled loop antenna, a zigzag monopole antenna, a zigzag dipole antenna and a microstrip antenna,
[0170] The dedicated area of each antenna part in the antenna wiring is 1000mm 2 the following,
[0171] The insulating film is a cured product of the present invention.
[0172] use Figure 1 An example of the antenna element of the present invention will be described. Figure 1 This is a schematic diagram of an example of a coplanar feed type microstrip antenna which is a type of planar antenna. Figure 1 a represents a cross-sectional view, Figure 1 b represents a top view. First, the formation method is described. The resin composition of the present invention is applied to the copper foil and pre-baked. Next, the copper foil is laminated and thermally cured to form a cured product including copper foil on both sides. Thereafter, the copper foil on one side is patterned using a subtractive method to obtain a cured product including Figure 1 b is an antenna element of an antenna pattern of a copper wiring of a microstrip line (MSL).
[0173] Secondly, Figure 1 The antenna pattern is shown in Figure 1. Figure 1 In a, the insulating film 16 is a substrate of the antenna and includes the cured product of the present invention. The ground 15 is a copper foil covering the entire surface of the insulating film 16. The antenna part 11, the matching circuit 12 and the MSL power supply line 13 on the upper layer of the insulating film 16 represent the cross section of the antenna wiring obtained by the patterning. The ground wiring thickness J and the antenna wiring thickness K can be any thickness according to the design of the impedance, but are generally 2μm to 20μm.
[0174] The antenna unit 11, the matching circuit 12, and the MSL power supply line 13 are arranged as follows Figure 1 b. 14 indicates the power supply point. In order to achieve impedance matching between the antenna unit 11 and the MSL power supply line 13, the length M of the matching circuit 12 has a length of 1 / 4λr (λr = (wavelength of the transmission wave) / (dielectric constant of the insulating material) 1 / 2 ). In addition, the width W and length L of the antenna portion 11 are designed to be 1 / 2λr. The length L of the antenna portion can be set to be less than 1 / 2λr according to the impedance design. By using the hardened material of the present invention on the substrate, a highly reliable antenna element that does not produce cracks even after the packaging reliability test can be provided. In addition, based on these characteristics, the antenna element using the insulating film of the present invention is suitable as an antenna for high frequencies, and the area of the antenna portion (=L×W) is set to 1000mm 2 By reducing the size to the following, a small antenna element can be formed. In this way, a high-efficiency, high-gain, small-sized antenna element for high frequencies can be obtained.
[0175] Another aspect of the electronic component of the present invention is an electronic component including a semiconductor package including at least a semiconductor element, a redistribution layer, a sealing resin, a ground wiring, and an antenna wiring. The electronic component is preferably:
[0176] The redistribution layer includes copper wiring and an insulating film, and the sealing resin is located between the ground wiring and the antenna wiring.
[0177] The insulating layer of the redistribution layer and / or the sealing resin is a cured product of the present invention.
[0178] As an example of the electronic component, Figure 2 A semiconductor package including an IC chip (semiconductor element), a redistribution layer, a sealing resin, and an antenna wiring is described. Figure 2 The schematic diagram of the cross section of a semiconductor package including an IC chip (semiconductor element), a rewiring layer, a sealing resin, and an antenna element. A rewiring layer (two layers of copper wiring and three layers of insulating film) formed by copper wiring 209 and an insulating film 210 formed by a hardened material of the present invention is formed on an electrode pad 202 of an IC chip 201. A barrier metal 211 and a solder bump 212 are formed on the pad of the rewiring layer (copper wiring 209 and insulating film 210). In order to seal the IC chip 201, a first sealing resin 208 formed by a hardened material of the present invention is formed, and a grounding copper wiring 206 for an antenna is formed thereon. A first through-hole wiring 207 is formed to connect the ground wiring 206 to the rewiring layer (copper wiring 209 and insulating film 210) via a through hole formed in the first sealing resin 208. A second sealing resin 205 formed of a hardened material of the present invention is formed on the first sealing resin 208 and the ground wiring 206, and a planar antenna wiring 204 is formed thereon. A second through-hole wiring 203 is formed to connect the planar antenna wiring 204 to the redistribution layer (copper wiring 209 and insulating film 210) via through holes formed in the first sealing resin 208 and the second sealing resin 205. The thickness of each layer of the insulating film 210 is preferably 10 μm to 20 μm, and the thickness of the first sealing resin and the second sealing resin are preferably 50 μm to 200 μm and 100 μm to 400 μm, respectively. Since the hardened material of the present invention deteriorates little after a reliability test, a semiconductor package including the obtained antenna element can be obtained with high reliability without cracks.
[0179] Example
[0180] Hereinafter, the present invention will be described with reference to Examples, but the present invention is not limited to these Examples. First, the evaluation method in each Example and Comparative Example will be described.
[0181] (1) Molecular weight determination
[0182] The weight average molecular weight (Mw) of the component (A) was confirmed using a GPC (gel permeation chromatography) apparatus Waters 2690-996 (manufactured by Waters Japan Co., Ltd.). The developing solvent was set to N-methyl-2-pyrrolidone (hereinafter referred to as NMP (N-methyl-2-pyrrolidone)) for measurement, and the weight average molecular weight (Mw) and the dispersion degree (PDI = Mw / Mn) were calculated in terms of polystyrene.
[0183] (2) Determination of dielectric loss tangent
[0184] The varnish was applied to a copper foil (NA-VLP thickness 15 μm: manufactured by Mitsui Kinzoku Co., Ltd.) using a rod coater (manufactured by Hohsen Co., Ltd.) in such a way that the film thickness after pre-baking was 20 μm, and dried at 100°C for 30 minutes. Thereafter, an inert oven (CLH-21CD-S manufactured by Koyo Thermo System Co., Ltd.) was used to raise the temperature to 220°C at 3.5°C / min at an oxygen concentration below 20 ppm, and heat treatment was performed at each temperature for 1 hour. The copper foil was taken out when the temperature was below 50°C, and was etched away using an aqueous solution of ferric chloride to obtain a cured product. The film was cut into strips of 3 cm in width and 10 cm in length, and the dielectric loss tangent at a frequency of 1 GHz was measured using a perturbation-type cavity resonator method in accordance with American Society for Testing and Materials (ASTM) D2520 at room temperature of 23.0°C and humidity of 45.0% RH. The evaluation criteria are as follows. The lower the dielectric loss tangent, the more likely it is to suppress transmission loss.
[0185] A: The value of dielectric loss tangent is less than 0.005
[0186] B: The dielectric loss tangent is 0.005 or more and less than 0.008
[0187] C: The dielectric loss tangent is 0.008 or more and less than 0.012
[0188] D: The value of dielectric loss tangent is 0.012 or more.
[0189] (3) Determination of the linear thermal expansion coefficient of the cured product
[0190] A self-supporting film of the cured product was prepared in the same manner as in the above-mentioned "(2) Determination of Dielectric Loss Tangent", and the film was cut out with a single blade in a manner of 0.5 cm in width and 3.0 cm in length, and measured using a thermomechanical analyzer (manufactured by Seiko Instruments, TMA / SS6100) under a nitrogen flow and 80 mL / min conditions, with the temperature raised from 25°C to 400°C at a rate of 10°C / min. The evaluation criteria are as follows. The lower the linear thermal expansion coefficient, the less warping with respect to the substrate.
[0191] A: The value of linear thermal expansion coefficient is less than 25ppm
[0192] B: The value of the linear thermal expansion coefficient is 25 ppm or more and less than 40 ppm
[0193] C: The value of the linear thermal expansion coefficient is 40 ppm or more and less than 60 ppm
[0194] D: The value of the linear thermal expansion coefficient is 60 ppm or more.
[0195] (4) Evaluation of coating properties
[0196] After the varnish was spin-coated on a 4-inch silicon wafer using a spin coater (1H-360S manufactured by Mikasa Co., Ltd.), it was pre-baked at 120°C for 3 minutes using a hot plate (SCW-636 manufactured by Dainippon Screen Co., Ltd.) to prepare a pre-baked film with a film thickness of 11 μm. For the pre-baked film, a surface roughness measuring instrument (SURFCOM 1400D manufactured by Tokyo Seimitsu Co., Ltd.) was used to measure the range of ±20 mm from the center of the wafer. The height difference (Ttop) at the center and the position 20 mm from the center was measured and evaluated. The evaluation criteria are as follows.
[0197] A: Ttop value is 0μm or more and less than 5μm
[0198] B: Ttop value is 5μm or more and less than 15μm
[0199] C: Ttop value is 15μm or more and less than 35μm
[0200] D: Ttop value is 35μm or more and less than 50μm
[0201] E: Ttop value is 50 μm or more.
[0202] In addition, the appearance of the obtained sample was visually observed to visually confirm the presence or absence of aggregates. The evaluation criteria are as follows.
[0203] A: No condensate
[0204] B: Very few agglomerates (no problem in practical use)
[0205] C: Agglomerates are present (a level that is problematic for practical use).
[0206] (5) Evaluation of chemical resistance
[0207] After the varnish was spin-coated on a 4-inch silicon wafer using a spin coater (1H-360S manufactured by Mikasa Co., Ltd.), it was pre-baked at 120°C for 3 minutes using a hot plate (SCW-636 manufactured by Dainippon Screen Co., Ltd.) to prepare a pre-baked film with a film thickness of 11 μm. Thereafter, the temperature was raised to 220°C at 3.5°C / min at an oxygen concentration of less than 20 ppm using an inert oven (CLH-21CD-S manufactured by Koyo Thermo System Co., Ltd.) for 1 hour for heat treatment. The silicon wafer was taken out when the temperature was less than 50°C, and the cured film was immersed in an organic chemical solution (dimethyl sulfoxide: 25% tetramethylammonium hydroxide (TMAH) aqueous solution = 92:2) at 65°C for 60 minutes to observe whether the film peeled off or dissolved. The evaluation criteria are as follows.
[0208] A: No pattern peeling, and film thickness change (indicating swelling or dissolution) is less than 5%
[0209] B: No pattern peeling, film thickness change is more than 5% and less than 20%
[0210] C: The pattern peels off and no film remains or the film thickness changes by more than 20%
[0211] Hereinafter, the abbreviations of the compounds used in Synthesis Examples and Examples are described.
[0212] ODPA: 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride
[0213] PBOM: 1,1'-(4,4'-oxybenzoyl)diimidazole
[0214] TFMB: 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl
[0215] 6FAP: 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane
[0216] Priamine 1075: a diamine compound containing a dimer of the compound represented by the formula (3) (trade name, manufactured by Croda Japan Co., Ltd.) (average amine value: 205)
[0217] MAP: meta-aminophenol
[0218] OPE-2st-1200: Oligophenylene ether (number average molecular weight: 1200) (manufactured by Mitsubishi Gas Chemical Co., Ltd.)
[0219] MIR-3000-70MT: Biphenyl aralkyl type maleimide compound (manufactured by Nippon Kayaku Co., Ltd.)
[0220] Ricon 130MA8: Maleic acid-modified polybutadiene resin (number average molecular weight: 2700) (manufactured by Total Lubricants Japan)
[0221] Cyclotene 4026-46: Benzocyclobutene solution (trade name, manufactured by Dow Chemical)
[0222] NC-3000: Epoxy resin (manufactured by Nippon Kayaku Co., Ltd.)
[0223] YC100C: Silica particles (trade name, manufactured by Admatechs, average particle size 100 nm)
[0224] SO-E1: Silica particles (trade name, manufactured by Admatechs, average particle size 0.3 μm)
[0225] SO-E5: Silica particles (trade name, manufactured by Admatechs, average particle size 1.5 μm)
[0226] FB-3SDC: Silica particles (trade name, manufactured by Denka Co., Ltd., average particle size 3.0 μm)
[0227] FB-8S: Silica particles (trade name, manufactured by Denka Co., Ltd., average particle size 6.7 μm)
[0228] AA04: Alumina particles ("Sumicorundum (registered trademark)" AA04, manufactured by Sumitomo Chemical Industries, Ltd., average particle size 0.4 μm)
[0229] UHP-S2: Boron nitride particles ("SHOBN (registered trademark)" UHP-S2, manufactured by Showa Denko Co., Ltd., average particle size 0.7 μm)
[0230] KBM-573: N-phenyl-3-aminopropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd.)
[0231] NMP: N-methyl-2-pyrrolidone
[0232] EL: Ethyl lactate
[0233] PGMEA: Propylene glycol methyl ether acetate
[0234] EGMEA: Ethylene glycol monomethyl ether acetate
[0235] L-1980N: a silicone-based surfactant ("Disparlon (registered trademark)" L-1980N, manufactured by Kusumoto Chemicals Co., Ltd.).
[0236] [Synthesis Example 1 Synthesis of polyimide (P-1)]
[0237] Under a dry nitrogen stream, 31.02 g (0.100 mol) of ODPA was dissolved in 234.67 g of NMP at 60°C. 1.09 g (0.010 mol) of MAP and 5 g of NMP were added simultaneously, and the mixture was reacted at 60°C for 15 minutes. Thereafter, 8.04 g (0.028 mol in terms of amino group) of Priamine 1075, 25.93 g (0.081 mol) of TFMB, and 20 g of NMP were added simultaneously, and the mixture was reacted at 60°C for 2 hours. Subsequently, the mixture was heated to 200°C and reacted for 3 hours. After the reaction was completed, the mixture was cooled to room temperature, and the solution was added to 3 L of water to obtain a white precipitate. The precipitate was collected by filtration, washed with water 3 times, and then dried in a ventilated dryer at 50°C for 3 days to obtain a powder of polyimide (P-1).
[0238] [Synthesis Example 2: Synthesis of polyimide precursor (P-2)]
[0239] Under a dry nitrogen stream, 31.02 g (0.100 mol) of ODPA was dissolved in 234.67 g of NMP at 60°C. 1.09 g (0.010 mol) of MAP and 5 g of NMP were added simultaneously, and the mixture was reacted at 60°C for 15 minutes. Thereafter, 8.04 g (0.028 mol in terms of amino group) of Priamine 1075, 25.93 g (0.081 mol) of TFMB, and 20 g of NMP were added simultaneously, and the mixture was reacted at 60°C for 2 hours. Thereafter, a solution prepared by diluting 21.45 g (0.180 mol) of N,N-dimethylformamide dimethyl acetal (manufactured by Mitsubishi Rayon Co., Ltd.) with 20 g of NMP was added dropwise over 10 minutes. After the addition, the mixture was stirred at 60°C for 3 hours. After the reaction was completed, the mixture was cooled to room temperature, and the solution was added to 3 L of water to obtain a white precipitate. The precipitate was collected by filtration, washed with water three times, and then dried in a 50° C. ventilation dryer for 3 days to obtain a powder of a polyimide precursor (P-2).
[0240] [Synthesis Example 3 Synthesis of polyamide (P-3)]
[0241] Under a dry nitrogen stream, 22.93 g (0.100 mol) of PBOM was dissolved in 234.67 g of NMP at 60°C. 1.09 g (0.010 mol) of MAP and 5 g of NMP were added simultaneously, and the mixture was reacted at 85°C for 15 minutes. Thereafter, 8.04 g (0.028 mol of amino group) of Priamine 1075, 25.93 g (0.081 mol) of TFMB, and 20 g of NMP were added simultaneously, and the mixture was reacted at 85°C for 3 hours. After the reaction was completed, the mixture was cooled to room temperature, and the solution was added to 3 L of water to obtain a white precipitate. The precipitate was collected by filtration, washed with water 3 times, and then dried in a ventilated dryer at 50°C for 3 days to obtain a powder of polyamide (P-3).
[0242] [Synthesis Example 4: Synthesis of polybenzoxazole precursor (P-4)]
[0243] Under a dry nitrogen stream, 22.93 g (0.100 mole) of PBOM was dissolved in 234.67 g of NMP at 60°C. 1.09 g (0.010 mole) of MAP and 5 g of NMP were added at the same time, and the mixture was reacted at 85°C for 15 minutes. Thereafter, 8.04 g (0.10 mole in terms of amino group) of Priamine 1075, 29.67 g (0.081 mole) of 6FAP, and 20 g of NMP were added at the same time, and the mixture was reacted at 85°C for 3 hours. After the reaction was completed, the mixture was cooled to room temperature, and the solution was added to 3 L of water to obtain a white precipitate. The precipitate was collected by filtration, washed with water 3 times, and dried in a ventilated dryer at 50°C for 3 days to obtain a powder of a polybenzoxazole precursor (P-4).
[0244] [Synthesis Examples 5 to 7: Synthesis of Polyimides (P-5) to (P-7)]
[0245] Polyimides (P-5) to (P-7) were synthesized in the same manner as in Synthesis Example 1 at the molar ratios shown in Table 1 below.
[0246] [Table 1]
[0247] [Table 1]
[0248]
[0249] [Examples 1 to 26 and Comparative Examples 1 to 6]
[0250] The components and blending amounts shown in Table 2-1, Table 2-2, Table 2-3 and Table 2-4 were mixed and stirred with a stirrer to obtain a varnish. The linear thermal expansion coefficient, dielectric loss tangent and coating properties of the obtained varnish were evaluated by the above-mentioned evaluation method. The evaluation results are shown in the following Tables 2-1 to 2-4.
[0251] [Table 2-1]
[0252] [Table 2-1]
[0253]
[0254] [Table 2-2]
[0255] [Table 2-2]
[0256]
[0257] [Table 2-3]
[0258] [Table 2-3]
[0259]
[0260] [Table 2-4]
[0261] [Table 2-4]
[0262]
[0263] Explanation of symbols
[0264] 1a: Section view
[0265] 1b: Top view
[0266] 11: Antenna
[0267] 12: Matching circuit
[0268] 13: MSL power supply line
[0269] 14: Power supply point
[0270] 15: Grounding
[0271] 16: Insulation film
[0272] J: Ground wiring thickness
[0273] K: Antenna wiring thickness
[0274] L: Antenna length
[0275] M: matching circuit length
[0276] W: antenna width
[0277] 201: IC chip
[0278] 202: Electrode pad
[0279] 203: Second through hole wiring
[0280] 204: Planar antenna wiring
[0281] 205: Second sealing resin
[0282] 206: Ground wiring
[0283] 207: First through hole wiring
[0284] 208: First sealing resin
[0285] 209: Copper wiring
[0286] 210: Insulation film
[0287] 211: Barrier Metal
[0288] 212: Solder Bump
Claims
1. A resin composition comprising: (A) a resin comprising at least one selected from the group consisting of polyimide, polybenzoxazole, their precursors, polyamide, and copolymers thereof; (B) inorganic particles having an average particle size of 150 nm or more and 5 μm or less; and (C) an ester solvent, and in the resin composition, The component (A) contains a diamine residue represented by the following formula (1) and / or a diamine residue represented by the following formula (2). When the content of the component (B) in the resin composition is Bm (mass), and the content of the component (C) is Cm (mass), 0.1≦(Bm / Cm)≦3.0 is satisfied, [Chemistry 1] (In formula (1), a, b, c and d are integers greater than 1 that satisfy a+b=6 to 17 and c+d=8 to 19, and the dotted line portion indicates a carbon-carbon single bond or a carbon-carbon double bond) [Chemistry 2] (In formula (2), e, f, g and h are integers greater than or equal to 1 satisfying e+f=6 to 17, g+h=8 to 19, and the dotted line portion indicates a carbon-carbon single bond or a carbon-carbon double bond).
2. The resin composition according to claim 1, wherein the total content of the diamine residue represented by formula (1) and the diamine residue represented by formula (2) in 100 mol% of all diamine residues in the component (A) is in the range of 1 mol% to 30 mol%. 3 . The resin composition according to claim 1 , wherein the content of the component (B) is 50% by mass or more and 80% by mass or less when the solid content in the resin composition is 100% by mass. 4 . The resin composition according to claim 1 , wherein the content of the component (C) is 40% by mass or more when the total amount of the solvent in the resin composition is 100% by mass. 5 . The resin composition according to claim 1 , wherein the component (C) comprises a glycol ester solvent. 6 . The resin composition according to claim 1 , wherein the component (C) is a glycol ester solvent, and when the total amount of the solvent in the resin composition is 100% by mass, the content of the component (C) is 40% by mass or more. 7 . The resin composition according to claim 1 , wherein the component (B) is inorganic particles having an average particle diameter of 150 nm to 1 μm.
8. The resin composition according to claim 1 or 2, wherein the resin composition further contains a thermosetting resin as component (D), The component (D) contains at least one selected from the group consisting of polyphenylene ether resin, maleimide resin, polybutadiene resin, and benzocyclobutene resin.
9. A cured product obtained by curing the resin composition according to claim 1 or 2.
10. An electronic component comprising the hardened material according to claim 9. 11 . An electronic component comprising two or more layers of wiring and an insulating film, wherein the insulating film is disposed between the two or more layers of wiring, and the insulating film is the cured product according to claim 9 .
12. An antenna element comprising at least one antenna wiring, a ground, and an insulating film for insulating the ground from the antenna wiring, wherein: The antenna wiring includes at least one selected from the group consisting of a zigzag loop antenna, a coiled loop antenna, a zigzag monopole antenna, a zigzag dipole antenna and a microstrip antenna, The dedicated area of each antenna part in the antenna wiring is 1000mm 2 the following, The insulating film is the cured product according to claim 9.
13. An electronic component comprising a semiconductor package including at least a semiconductor element, a redistribution layer, a sealing resin, a ground wiring, and an antenna wiring, wherein: The redistribution layer includes copper wiring and an insulating film, and the sealing resin is located between the ground wiring and the antenna wiring. The insulating layer of the redistribution layer and / or the sealing resin is the cured product according to claim 9 .
Citation Information
Patent Citations
Photosensitive resin composition
JP2018036329A
Resin composition and resin film
JP2021105146A